Performance of the Alcohol Use Disorders Identification Test Among Tuberculosis Patients in Russia - Mathew, Trini; Shields, Alan; Yanov, Sergey; Golubchikova, Vera; Strelis, Aivar; Yanova, Galina; Mishustin, Sergey; Fitzmaurice, Garrett; Connery, Hilary; Shin, Sonya; Greenfield, Shelly F. (Substance use & misuse, 2010)
The alcohol use disorders identification test (AUDIT), a screening instrument to identify individuals at risk of alcohol use-related problems, has not been validated in a Russian primary care population. We assessed the reliability, factor structure, sensitivity, and specificity of AUDIT scores among 254 subjects initiating tuberculosis treatment from 2005 to 2007 in Tomsk City. Our findings support the use of the AUDIT as a screening instrument among Russian individuals seeking primary care. We discuss implications, limitations, and future research.